Unsupervised Anomaly Detection for Space Gardening - Rewicki, Ferdinand; Denzler, Joachim; Niebling, Julia (2023)
Bioregenerative Life Support Systems (BLSS) will be used within extra-terrestrial habitats to produce food, close material cycles (respiratory air, water, biomass, waste), and enhance well-being. The EDEN NEXT GEN project aims at designing an integrated BLSS ground demonstrator including all critical subsystems. Therefore, it builds on the results gained at the research greenhouse EDEN ISS in Antarctica between 2018 and 2021. To ensure safe and stable operation, we are researching unsupervised anomaly detection (USAD) methods to identify unhealthy system states. While the abundance of available methods makes it difficult to choose the most appropriate method for a specific application, each method has its strengths in detecting anomalies of different types. We validate our previous findings in the BLSS domain and apply the best-performing methods to telemetry data collected from the EDEN ISS research greenhouse.